1998
DOI: 10.1021/jo972227r
|View full text |Cite
|
Sign up to set email alerts
|

Hemirubin:  An Intramolecularly Hydrogen-Bonded Analogue for One-Half Bilirubin

Abstract: A model for one-half bilirubin, the neurotoxic yellow-orange pigment of jaundice, 9-[2-(2-carboxyethyl)benzyl]-2,3,7,8-tetramethyl-1,10-dihydrodipyrrin (1, hemirubin) was synthesized following SnCl(4)-catalyzed Friedel-Crafts acylation at C(9) of 2,3,7,8-1-oxo-1,10-dihydrodipyrrin (7) with methyl o-(chlorocarbonyl)hydrocinnamate. Unlike earlier bilirubin model compounds, hemirubin is predicted and found to engage in intramolecular hydrogen bonding. Like bilirubin, the propionic acid carboxyl group of hemirubin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…[28][29][30] To mimic BR's intramolecular hydrogen bonding in single dipyrrinone units, on the other hand, compounds with flexible alkane chains have been synthesized and proven to engage in internal hydrogen bonding. [31][32][33] The twisting motion of bilirubin has been identified as a deactivation channel in several studies 15,17,34,35 and confirmed by synthesis of N,N′-bridged dipyrrinones. 36 These show strong fluorescence in the case of a short methano bridge (φ fl ) 0.81), rapidly decreasing with increasing bridge length (φ fl ) 0.26 for ethano and φ fl ) 0.0012 for propano bridge), i.e., decreasing fluorescence with increasing rotational flexibility around the exocyclic bonds.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…[28][29][30] To mimic BR's intramolecular hydrogen bonding in single dipyrrinone units, on the other hand, compounds with flexible alkane chains have been synthesized and proven to engage in internal hydrogen bonding. [31][32][33] The twisting motion of bilirubin has been identified as a deactivation channel in several studies 15,17,34,35 and confirmed by synthesis of N,N′-bridged dipyrrinones. 36 These show strong fluorescence in the case of a short methano bridge (φ fl ) 0.81), rapidly decreasing with increasing bridge length (φ fl ) 0.26 for ethano and φ fl ) 0.0012 for propano bridge), i.e., decreasing fluorescence with increasing rotational flexibility around the exocyclic bonds.…”
Section: Introductionmentioning
confidence: 80%
“…In order to elucidate bilirubin's chemistry, complicated by exciton coupling and hydrogen bonding, model compounds as xanthobilirub(in)ic acid, XBR, and its methyl ester, MeXBR, have been synthesized and used in several studies. Due to the structural similarities with BR, even these dipyrrinone compounds tend to form hydrogen bonds by dimerization in nonpolar solvents. To mimic BR's intramolecular hydrogen bonding in single dipyrrinone units, on the other hand, compounds with flexible alkane chains have been synthesized and proven to engage in internal hydrogen bonding. …”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with earlier studies 1,2,17,19,20 showing that dipyrrinones are avid hydrogen bonders that bind strongly to one another as intermolecularly hydrogen-bonded dimers, except when a carboxylic acid is attached to an appropriate site on the dipyrrinone backbone. In that event, the dipyrrinone preferentially hydrogen bonds either intramolecularly to the carboxylic acid [21][22][23][24] and is monomeric or forms a stack dimer. [25][26][27] Consistent with those observations unless self-aggregation is promoted, 28 bilirubins are typically monomeric, 17 but analogs lacking carboxylic acid groups, eg, dimethyl esters and those with alkyl groups in place of CO 2 H are dimeric.…”
Section: Introductionmentioning
confidence: 99%
“…The HEME disintegration proceeds first through bilirubin and next into biliverdin that are composed of the dipyrromethene and dipyrromethane fragments, correspondingly. The transition from bilirubin to biliverdin is grounded by stereo conformational changes and interactions like hydrogen bonds. , Despite a great number of biological studies of polypyrroles, the description of the hydrogen bonding (HB) and proton transfer (PT) in these compounds is far from being comprehensive. This paper aims at filling this gap and presents the study of dipyrromethene (DP) and dipyrromethane (DP-1), Scheme , which vary basically in terms of intramolecular hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%